[OP.6A.04] HIGH PREVALENCE OF MASKED UNCONTROLLED HYPERTENSENSION AMONG TREATED PATIENTS FOLLOWED UNDER ROUTINE CANADIAN CLINICAL CARE. (September 2017) - Cloutier, L.; Guay, D.; Hamel, R.; Psaradellis, E.; Rampakakis, E.; Sampalis, J.
Abstract : Objective: Masked hypertension (MH), defined as elevated ambulatory blood pressure (BP) among patients with seemingly well controlled office blood pressure measurements (OBPM), has been associated with high cardiovascular risk. Previous studies have reported a MH prevalence between 10% to 30%, mostly among untreated individuals. The main objective of this study was to describe the prevalence of MH in borderline controlled hypertensive patients treated with short-acting antihypertensives in Canadian routine clinical care. Furthermore, differences between OBPM and home BP measurements (HBPM) taken 24-hours after last medication dose were assessed in treated hypertensive patients with borderline and almost controlled BP. Design and method: Real-life, prospective Canadian study conducted in general practitioners' offices. Enrolled patients had borderline (SBP 130–139 and/or DBP 80–89 mmHg) or almost controlled (SBP 140–149 and/or DBP 90–99 mmHg) BP based on OBPM and were treated with short-acting antihypertensives. Patients collected HBPMs for 7 consecutive days. MH was defined as HBPM SBP > = 135 and/or DBP > = 85 mmHg among borderline controlled patients. Results: 983 patients were included; 370 (37.6%) were borderline controlled and 613 (62.4%) were almost controlled. Mean (SD) age was 60.5 (11.0) years, 50.1% were male and 65.7% were Caucasian without any remarkable differences between groups. OBPM and HBPM values are summarized in Table 1. Among patients with borderline controlled OBPM hypertension, 187 (50.5%) had MH. Figure. No caption available. Conclusions: A higher rate of MH than what was previously reported in the literature was observed in this study, which confirms previous studies suggesting that the use of short-acting antihypertensives may be a risk factor for MH, probably due to suboptimal coverage over 24 hours. These results support the latest Canadian Hypertension Education Program recommendations that OBPM alone is inadequate for BP control optimization.